Improving the dynamical behaviour of a laser cutting equipment by using a carbon fibre composite main structural runway frame - Vieira, D. G. (2013)
In order to improve the dynamic behaviour of an industrial laser cutting equipment a sandwich solution, using a carbon fibre reinforced polymer (CFRP) and polyester foam core, was implemented to construct its main runway structural frame, which supports the cutting head and major laser beam mirrors and lens. Nowadays, the commercial competiveness of laser cutting equipments is considerable enhanced by their higher cutting speed and precision, as well as, cost. With the recent available higher power laser beam generators and swifter motors quicker and powerful cuts may be already done. However, at accelerations of 3 and 4 g’s already enabled by linear motors, the lack of stiffness and high mass and consequent inertia of the traditional runway structural frames, made from steel and/or aluminium, do not allow achieving high required cutting precisions. Thus, the present study considered replacing those conventional materials by much lighter advanced CRFP composites to improve the dynamic performance of an existing laser cutting equipment. Advanced numeric Finite Element Method (FEM) calculations by using the ANSYS package software were made to verify the static and dynamic behaviours of the new composite structural frame and compare them to simulations made with the currently used steel solution.The composite structural frame processing method has been also studied and defined in this work. Furthermore, the composite laminate has been optimised by defining the better number of stacking layers and fibre orientations to be used, as well as, the foam core thickness. The failure of the new sandwich structural composite runway frame has been verified through the Tsai-Wu criterion. Finally, an economic analysis of the viability of the new composite solution adopted will be also presented.